Morphological Study of The Liliba River Utilizing Remote Sensing System - Anmuni, Avilla Martha; Loden, Onisius; Rafael, Jusuf Wilson Meynerd (Institut Teknologi Dirgantara Adisutjipto, 2024)
The branch of natural sciences called river morphology focuses on the study of the characteristics and dynamics of rivers, including their structure, classification, and changes on spatial and temporal scales. Two main factors influence river configurations. The first is natural factors, such as floods and landslides, and the second is human factors, such as human activities that alter river morphology. Cyclone Seroja caused landslides on the banks of the Liliba River in Kupang, East Nusa Tenggara in April 2022. This mainly occurred at Naimata Bridge in Liliba Village, Oebobo District. River geometry, especially the channel and bed elevation, can be significantly influenced by landslides occurring on the riverbanks. Therefore, a study of the morphology of the Liliba River was conducted using remote sensing systems. To conduct a detailed analysis, this study incorporated these photos. In this review, changes in the river channel were examined by extracting the river's course from Landsat image data. From 2009 to 2022, the Liliba River experienced an average shift of 1.60 meters westward and eastward. The research results indicate the need for reforestation along the riverbanks, and residents should be encouraged to reduce the disposal of plastic waste into the river. Future research should also further investigate the geological characteristics of the Liliba River, such as rock types, and conduct hydrological analyses to comprehensively understand the factors influencing changes in the riverbed.